Farm diversity, classification schemes and multifunctionality - van der Ploeg, J.D.; Laurent, C.; Blondeau, F.; Bonnafous, P. (Journal of environmental management, 2009)
Diversity is not only intrinsic to agriculture; it can be considered also as one of its main assets as it provides a wide range of responses that can help to face uncertain futures. The ongoing encounter between changing spatial and temporal frameworks and a set of diverse farming strategies is leading to the emergence of an ongoing flow of development models that could materialize in a wide range of farming practices, contrasting enterprise models, changing relations between rural households and agricultural holdings, and differentiated patterns that link farming and farming families to the wider context in which they are embedded. The many-sided diversity encountered in agriculture is not only the outcome of the agency and polyvalence of the actors involved; their agency and polyvalence are in turn inspired and strengthened by the material and symbolic diversity, which contributes to a further unfolding of diversity. A proper understanding of the range, dimensions, significance and causes of diversity has been, over the centuries, a main concern—first for what is now known as classical agronomy, and later on in agrarian sciences. Yet the classification schemes, developed and used for such an understanding, have increasingly become an Achilles heel as each of them relies on specific assumptions that will bring out particular features of the overall farm diversity and will result in different perspectives of what agriculture is and how it fits into societal projects. Consequently, they are at the core of many debates and struggles, not only within agrarian sciences but increasingly on a wider societal level. The growing recognition of multifunctionality in agriculture, especially in the context of the changing EU policy, strengthens the relevance and importance of this debate. In this new context, we discuss advantages and limits of different classification principles by comparing two methodologies which have been extensively used in France and the Netherlands.